Comparative Study in Central and Eastern Europe Regarding Restitution/Compensation Process - Bejtja, Saida; Bejtja, Dritan (European Journal of Economics and Business Studies, 2015)
The aim of this paper is to analyze the transformations that occurred in the area of private property ownership following the change of political regime in former socialist or communist countries. The six countries looked at are: Albania, Bulgaria, Croatia, Romania and Serbia. These countries illustrate well the whole range of contentious problems in a region where the Communist regimes have varied tremendously in their approach to private property, intensity of social control, repression and overall legitimacy. This diversity of situations poses today different types of dilemmas for the property restitution process, dilemmas which are approached by each country in a different manner. The main question for the countries is how an emerging democracy can "respond to public demands for redress of the legitimate grievances of some without creating new injustices for others. " Moreover, property rights and transparency represent the very bases of a functioning market economy: each of the countries faces the difficult task of finding a balance between remedying violations of property rights and guaranteeing a functioning land market, which enables or will enable full freedom of movement of capital in the EU. There are a number of fundamental difficulties and dilemmas regarding nationalization and restitution/compensation policies in the post-Communist governments in Albania, Bulgaria, Romania and the Western Balkans had to face.